Synthesis method and application of catalyst for preparing vinyl chloride through catalytic cracking of 1, 2-dichloroethane
By loading metal chlorides on nitrogen-doped carbon spots as catalysts, the problems of high energy consumption and catalyst ease in the existing vinyl chloride production methods are solved, and the high conversion rate of 1,2-dichloroethane and chlorine are achieved. The high yield of ethylene, catalyst selectivity and stability have been significantly improved.
Patent Information
- Application Number
- CN202411488824.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing vinyl chloride production methods have problems such as high energy consumption, easy coking, and short production cycles, and the catalyst is prone to deactivate, making it difficult to achieve high-efficiency cracking in low temperatures.
The catalyst is improved by uniformly dispersing the active components on the nitrogen-doped carbon dots supported on the activated carbon.
The high conversion rate of 1,2-dichloroethane and high yield of vinyl chloride are achieved, and the catalyst selectivity and stability are good, and it can perform efficient catalytic cracking at lower temperatures.
Abstract
Description
Technical Field
[0001] The present application relates to a method for synthesizing a catalyst for preparing vinyl chloride by catalytic cracking of 1,2-dichloroethane with high activity and its application, and belongs to the field of vinyl chloride monomer preparation. Background Art
[0002] As one of the five most common plastics used worldwide, polyvinyl chloride (PVC) plays an indispensable role in the fields of building materials, packaging materials, wires and cables, etc. The core of its production lies in the preparation of vinyl chloride monomer, and there are two main methods for preparing vinyl chloride: the acetylene method and the ethylene method.
[0003] The acetylene process for producing vinyl chloride usually relies on mercury catalysts. Although this method has been used in industrial production, the use of mercury catalysts not only leads to high investment costs, but also brings serious environmental pollution and health risks. Therefore, with the increase of environmental awareness and strict regulations, the acetylene process is gradually being replaced by more environmentally friendly and efficient methods.
[0004] The ethylene method has become the mainstream method for producing vinyl chloride. It mainly relies on the chlorination or oxychlorination of ethylene to produce 1,2-dichloroethane, and then obtains vinyl chloride through high-temperature cracking. However, although the high-temperature cracking method is mature, it has problems such as high energy consumption, easy coking, and short production cycle, which limit the further development of this method.
[0005] In recent years, researchers have conducted a lot of research on reducing cracking temperature and improving catalyst activity. Among them, catalytic cracking technology has attracted much attention because it can achieve efficient cracking at lower temperatures. Early research mainly focused on catalysts such as metal chlorides. Although these catalysts can reduce the cracking temperature to a certain extent, problems such as catalyst deactivation and high cracking temperature remain to be solved.
[0006] Patent CN113262794A discloses a combined catalyst, but the catalyst contains many types of metals and has a complicated preparation process, which is not conducive to mass production. Patent CN116251610A discloses a single-atom catalyst, in which the active center metal exists completely in the form of isolated single atoms on nitrogen-doped carbon materials, but the carbon material has poor dispersibility and is easy to agglomerate, and the catalyst active sites are less exposed.
[0007] With the deepening of research, the use of nitrogen-doped carbon dots to load metal chlorides has become a research hotspot. Due to the unique structure of carbon dots of 0 to 10 nm, the dispersion of metal active components can be greatly improved, the metal activity can be increased, and the doped nitrogen element also plays a key role in the catalytic cracking process.
[0008] As an emerging type of catalyst, nitrogen-doped carbon dots loaded with metal chlorides have also shown excellent performance in the cracking of 1,2-dichloroethane to vinyl chloride. Its highly dispersed active sites and unique electronic structure provide new possibilities for achieving low-temperature and efficient catalytic cracking. However, how to improve the activity of the catalyst and extend its service life is still the focus of current research.
[0009] In summary, with the increasing environmental protection requirements and the intensification of the energy crisis, the development of efficient and environmentally friendly vinyl chloride production methods has become an urgent need for the development of the industry. As a production method with potential, the research and application of catalytic cracking technology will have a profound impact on the sustainable development of the PVC industry. Summary of the invention
[0010] The present invention provides a method for synthesizing a catalyst for preparing vinyl chloride by catalytic cracking of 1,2-dichloroethane with high activity, wherein the active components in the catalyst are uniformly dispersed on nitrogen-doped carbon dots supported on activated carbon. The highly dispersed active sites provide new possibilities for achieving low-temperature and high-efficiency catalytic cracking. The catalyst is applied to the reaction of preparing vinyl chloride by cracking 1,2-dichloroethane, and has high 1,2-dichloroethane conversion rate, good catalyst selectivity, high vinyl chloride yield, and good stability.
[0011] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0012] A catalyst for catalytic cracking of 1,2-dichloroethane to prepare vinyl chloride. The catalyst uses activated carbon as a carrier and loads nitrogen-doped carbon dots containing active components. The mass percentage of the nitrogen-doped carbon dots containing active components is 15.2-30.1% based on the total mass of the catalyst.
[0013] The catalyst of the present invention, wherein the activated carbon is one or more of coal-based activated carbon, fruit shell activated carbon, and coconut shell activated carbon.
[0014] The catalyst of the present invention, wherein the active component is a metal chloride selected from CuCl 2 , CuCl, FeCl 3 、MnCl 3 、NiCl 2 、FeCl 2 、ZnCl 2 At least one of .
[0015] In the catalyst of the present invention, the nitrogen source in the nitrogen-doped carbon dots is at least one of acrylamide, urea, melamine, pyrrole and ammonium chloride.
[0016] In the catalyst of the present invention, the synthetic material of the carbon dots in the nitrogen-doped carbon dots is one of petroleum asphalt, coal asphalt and natural asphalt.
[0017] A method for synthesizing a catalyst for preparing vinyl chloride by catalytic cracking of 1,2-dichloroethane comprises the following steps:
[0018] (1) The condensed aromatic hydrocarbon solid, the active component and the nitrogen source are uniformly mixed together, calcined, oxidized and then dialyzed to obtain a carbon dot solution.
[0019] (2) Soaking activated carbon in carbon dot solution.
[0020] (3) The soaked activated carbon is heated and dried to evaporate the solvent (referring to the solution during dialysis, mainly water and peracid) and load the carbon dots onto the activated carbon.
[0021] (4) After the activated carbon loaded with carbon dots is dried, it is calcined at high temperature under an inert gas to obtain a catalyst for catalytic cracking of 1,2-dichloroethane to produce vinyl chloride.
[0022] In the step (1), the condensed aromatic hydrocarbon solid is at least one of petroleum asphalt, coal asphalt and natural asphalt, and the mass percentage of the condensed aromatic hydrocarbon solid is 30-50%, based on the mass sum of the condensed aromatic hydrocarbon solid, the active component and the nitrogen source, the same below;
[0023] In the step (1), the active component is CuCl 2 , CuCl, FeCl 3 、MnCl 3 、NiCl 2 、FeCl 2 、ZnCl 2 At least one of the following, with a mass percentage of 30 to 50%;
[0024] In the step (1), the nitrogen source is at least one of acrylamide, urea, melamine, pyrrole, and ammonium chloride, and the mass percentage is 10 to 30%;
[0025] In the step (1), calcination is carried out under normal pressure, with a heating rate of 1 to 10°C / min, a calcination temperature of 300 to 600°C, and a calcination time of 60 to 120 minutes;
[0026] In the step (1), the oxidation is carried out under normal pressure, the oxidant is a peracid, for example, a mixture of 150 parts by volume of formic acid and 10-30 parts by volume of hydrogen peroxide; the oxidation temperature is room temperature, and the oxidation time is 5 to 10 hours;
[0027] In the step (1), the dialysis is performed at room temperature and pressure using a 1000 Dalton dialysis bag for 24 to 48 hours.
[0028] In the step (2), the activated carbon is at least one of coal-based activated carbon, fruit shell activated carbon, and coconut shell activated carbon;
[0029] In the step (2), the immersion is carried out at room temperature and pressure, the immersion temperature is 30 to 80° C., and the immersion time is 24 to 48 hours.
[0030] In the step (3), the heating and drying temperature is 100-120° C. and the time is 24-48 hours. By heating and drying, the solvent (the solvent refers to the solution during dialysis, mainly water and peroxyacid) is completely evaporated, and the carbon dots are all loaded onto the activated carbon.
[0031] In the step (4), high-temperature calcination is carried out under an inert gas (referring to a gas that is inert to the reaction), with a heating rate of 1 to 10° C. / min, a high-temperature calcination temperature of 400 to 800° C., and a time of 5 to 12 hours.
[0032] The invention also relates to the application of the catalyst in catalyzing the cracking of 1,2-dichloroethane to produce vinyl chloride.
[0033] The beneficial effects of this application include, but are not limited to:
[0034] (1) The catalyst synthesis method provided in the present application has a simple preparation method and readily available raw materials; it greatly improves the dispersibility of the active components of the catalyst and increases the exposure area of the active components. In addition, nitrogen doping in the carbon dots can change the electronic structure of the active components, which is beneficial to the generation of reactive free radicals. Compared with existing nitrogen-doped carbon materials, it can greatly improve the catalyst activity.
[0035] (2) The catalyst prepared in the present application is used for cracking ethylene dichloride to produce vinyl chloride, with a high yield of vinyl chloride and good stability in the entire reaction process. DETAILED DESCRIPTION
[0036] The technical scheme of the present invention and its effects are further described below by specific examples. The following examples are only used to illustrate the content of the present invention and are not used to limit the protection scope of the present invention. Simple changes made to the present invention by applying the concept of the present invention are all within the scope of the protection claimed by the present invention.
[0037] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0038] Example 1
[0039] 1g coal tar, 0.5g melamine and 1g CuCl 2 Mix well in the porcelain boat, put the porcelain boat into a tube furnace, and heat it at 3℃min in a nitrogen atmosphere. -1 Heated to 350 °C and calcined at 350 °C for 90 min to obtain CuCl supported by nitrogen-doped carbon material. 2Catalyst precursor. Under ultrasonic conditions, the catalyst precursor was oxidized with a mixture of 150 ml of 88 wt% formic acid and 15 ml of 30 wt% hydrogen peroxide for 5 hours to obtain a catalyst nanoparticle solution. The solution was dialyzed in a 1000 Dalton dialysis bag for 48 hours to obtain nitrogen-doped carbon point-supported CuCl 2 Catalyst solution. Add coal-based activated carbon to the above solution and soak it under normal pressure so that the solution can fully penetrate into the activated carbon. The soaking temperature is 40°C and the soaking time is 24 hours. Dry the soaked activated carbon and its load at 120°C to fully evaporate the solvent. Calcine the dried activated carbon in a tubular furnace under nitrogen protection at a high temperature of 400°C and a heating rate of 3°C min. -1 , calcination time 6h. Then cool to room temperature.
[0040] The above operation was repeated several times until the mass of the prepared catalyst exceeded 35 g.
[0041] The 1,2-dichloroethane liquid was pumped into a fixed bed reactor filled with the 1,2-dichloroethane cracking catalyst prepared in this example. 35 g of the catalyst was placed in the reactor. The reactor temperature was 300° C. and the mass space velocity of 1,2-dichloroethane was 40 h / min. -1 The conversion rate of 1,2-dichloroethane was 33%, the selectivity of vinyl chloride was greater than 99%, and the catalyst was maintained for 40 hours without deactivation.
[0042] Example 2
[0043] 1.5g petroleum asphalt, 0.8g urea and 1g NiCl 2 Mix well in the porcelain boat, put the porcelain boat into a tube furnace, and heat it at 3℃min in a nitrogen atmosphere. -1 Heated to 350 °C and calcined at 350 °C for 90 min to obtain NiCl supported by nitrogen-doped carbon material. 2 Catalyst precursor. Under ultrasonic conditions, the catalyst precursor was oxidized with a mixture of 150 ml of 88 wt% formic acid and 15 ml of 30 wt% hydrogen peroxide for 5 hours to obtain a catalyst nanoparticle solution. The solution was dialyzed in a 1000 Dalton dialysis bag for 48 hours to obtain nitrogen-doped carbon point-loaded NiCl 2 Catalyst solution. Add coconut shell activated carbon to the above solution and soak it under normal pressure so that the solution can fully penetrate into the activated carbon. The soaking temperature is 40°C and the soaking time is 30 hours. Dry the soaked activated carbon and its load at 120°C to fully volatilize the solvent. Calcine the dried activated carbon in a tubular furnace under nitrogen protection at a high temperature of 600°C and a heating rate of 3°C min. -1 , calcination time 8h. Cool to room temperature.
[0044] The above operation was repeated several times until the mass of the prepared catalyst exceeded 35 g.
[0045] The 1,2-dichloroethane liquid was pumped into a fixed bed reactor filled with the 1,2-dichloroethane cracking catalyst prepared in this example. 35 g of the catalyst was placed in the reactor. The reactor temperature was 300 °C and the mass space velocity was 40 h -1 The conversion rate of 1,2-dichloroethane was 48%, the selectivity of vinyl chloride was greater than 99%, and the catalyst was maintained for 40 hours without deactivation.
[0046] Example 3
[0047] 2g coal tar, 1g acrylamide and 1.5g ZnCl 2 Mix well in the porcelain boat, put the porcelain boat into a tube furnace, and heat it at 4℃min in a nitrogen atmosphere. -1 Heated to 400 °C and calcined at 400 °C for 90 min to obtain nitrogen-doped carbon material supported ZnCl 2 Catalyst precursor. Under ultrasonic conditions, the catalyst precursor was oxidized with a mixture of 200 ml of 88 wt% formic acid and 15 ml of 30 wt% hydrogen peroxide for 5 hours to obtain a catalyst nanoparticle solution. The solution was dialyzed in a 1000 Dalton dialysis bag for 48 hours to obtain nitrogen-doped carbon point-loaded ZnCl 2 Catalyst solution. Add coal-based activated carbon to the above solution and soak it under normal pressure so that the solution can fully penetrate into the activated carbon. The soaking temperature is 50°C and the soaking time is 40 hours. Dry the soaked activated carbon and its load at 120°C to fully volatilize the solvent. Calcine the dried activated carbon in a tubular furnace under nitrogen protection at a high temperature of 500°C and a heating rate of 3°C min. -1 , calcination time 8h. Cool to room temperature.
[0048] The above operation was repeated several times until the mass of the prepared catalyst exceeded 35 g.
[0049] The 1,2-dichloroethane liquid was pumped into a fixed bed reactor filled with the 1,2-dichloroethane cracking catalyst prepared in this example. 35 g of the catalyst was placed in the reactor. The reactor temperature was 300 °C and the mass space velocity was 40 h -1 The conversion rate of 1,2-dichloroethane was 78%, the selectivity of vinyl chloride was greater than 99%, and the catalyst was maintained for 40 hours without deactivation.
[0050] Example 4
[0051] 2.5 g natural asphalt, 1 g pyrrole and 2 g MnCl 3Mix well in the porcelain boat, put the porcelain boat into a tube furnace, and heat it at 3℃min in a nitrogen atmosphere. -1 Heated to 500 °C and calcined at 500 °C for 90 min to obtain MnCl supported by nitrogen-doped carbon material. 3 Catalyst precursor. Under ultrasonic conditions, the catalyst precursor was oxidized with a mixture of 150 ml of 88 wt% formic acid and 15 ml of 30 wt% hydrogen peroxide for 5 hours to obtain a catalyst nanoparticle solution. The solution was dialyzed in a 1000 Dalton dialysis bag for 48 hours to obtain nitrogen-doped carbon point-supported MnCl 3 Catalyst solution. Add the fruit shell activated carbon to the above solution and soak it under normal pressure so that the solution can fully penetrate into the activated carbon. The soaking temperature is 60°C and the soaking time is 45 hours. Dry the soaked activated carbon and its load at 120°C to fully volatilize the solvent. Calcine the dried activated carbon in a tubular furnace under nitrogen protection at a high temperature of 600°C and a heating rate of 3°C min -1 , calcination time 6h, cooling to room temperature.
[0052] The above operation was repeated several times until the mass of the prepared catalyst exceeded 35 g.
[0053] The 1,2-dichloroethane liquid was pumped into a fixed bed reactor filled with the 1,2-dichloroethane cracking catalyst prepared in this example. 35 g of the catalyst was placed in the reactor. The reactor temperature was 300 °C and the mass space velocity was 40 h -1 The conversion rate of 1,2-dichloroethane was 59%, the selectivity of vinyl chloride was greater than 99%, and the catalyst was maintained for 40 hours without deactivation.
[0054] Example 5
[0055] Mix 2g coal tar, 1g ammonium chloride and 2g CuCl in a porcelain boat. Put the porcelain boat into a tube furnace. In a nitrogen atmosphere, heat the tube furnace at 3℃ min. -1 Heat to 300°C and calcine at 300°C for 90 minutes to obtain a CuCl catalyst precursor supported by nitrogen-doped carbon material. Under ultrasonic conditions, use 150 ml of a mixture of 88wt% formic acid and 15 ml of 30wt% hydrogen peroxide to oxidize the above catalyst precursor for 5 hours to obtain a catalyst nanoparticle solution. Dialyze the solution in a 1000 Dalton dialysis bag for 48 hours to obtain a CuCl catalyst solution supported by nitrogen-doped carbon dots. Add coal-based activated carbon to the above solution and soak it under normal pressure so that the solution can fully penetrate into the activated carbon. The soaking temperature is 80°C and the soaking time is 48 hours. Dry the soaked activated carbon and its load at 120°C to fully volatilize the solvent. The dried activated carbon is calcined at high temperature in a tubular furnace under nitrogen protection. The calcination temperature is 800°C and the heating rate is 3°C min-1 , calcination time 10h, cooling to room temperature.
[0056] The above operation was repeated several times until the mass of the prepared catalyst exceeded 35 g.
[0057] The 1,2-dichloroethane liquid was pumped into a fixed bed reactor filled with the 1,2-dichloroethane cracking catalyst prepared in this example. 35 g of the catalyst was placed in the reactor. The reactor temperature was 300 °C and the mass space velocity was 40 h -1 The conversion rate of 1,2-dichloroethane was 21%, the selectivity of vinyl chloride was greater than 99%, and the catalyst was maintained for 40 hours without deactivation.
[0058] Comparative Example 1
[0059] 2g coal tar, 1g melamine and 2g CuCl 2 Mix well in the porcelain boat, put the porcelain boat into a tube furnace, and heat it at 3℃min in a nitrogen atmosphere. -1 Heated to 350 °C and calcined at 350 °C for 90 min to obtain CuCl supported by nitrogen-doped carbon material. 2 Catalyst precursor. Grind 2g of the above material into powder and dilute it into an aqueous solution. Add coal-based activated carbon to the above solution and soak it under normal pressure so that the solution can fully penetrate into the activated carbon. The soaking temperature is 40°C and the soaking time is 24 hours. Dry the soaked activated carbon and its load at 120°C to fully evaporate the solvent. Calcine the dried activated carbon in a tubular furnace under nitrogen protection at a high temperature of 600°C and a heating rate of 3°C min -1 , calcination time 8h. Then cool to room temperature.
[0060] The above operation was repeated several times until the mass of the prepared catalyst exceeded 35 g.
[0061] The 1,2-dichloroethane liquid was pumped into a fixed bed reactor filled with the 1,2-dichloroethane cracking catalyst prepared in this example. 35 g of the catalyst was placed in the reactor. The reactor temperature was 300 °C and the mass space velocity was 40 h -1 The conversion rate of 1,2-dichloroethane was 2%, the selectivity of vinyl chloride was about 93%, and the catalyst was maintained for 40 hours without deactivation.
[0062] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for synthesizing a catalyst for preparing vinyl chloride by catalytic cracking of 1,2-dichloroethane, comprising the following steps: (1) uniformly mixing a condensed aromatic hydrocarbon solid, an active component and a nitrogen source, calcining, oxidizing, and then dialyzing to obtain a carbon dot solution; (2) immersing the activated carbon in a carbon dot solution; (3) heating and drying the soaked activated carbon to evaporate the solvent and load the carbon dots onto the activated carbon; (4) After drying the activated carbon loaded with carbon dots, calcining at high temperature under an inert gas to obtain the catalyst.
2. The method according to claim 1, wherein: In step (1), the condensed aromatic hydrocarbon solid is at least one of petroleum asphalt, coal asphalt and natural asphalt; Preferably, the mass percentage of the condensed aromatic hydrocarbon solid is 30-50%, based on the sum of the masses of the condensed aromatic hydrocarbon solid, the active component and the nitrogen source.
3. The method according to claim 1 or 2, wherein: In step (1), the active component is at least one of CuCl2, CuCl, FeCl3, MnCl3, NiCl2, FeCl2, and ZnCl2; Preferably, the mass percentage of the active component is 30-50%, based on the sum of the masses of the condensed aromatic hydrocarbon solid, the active component and the nitrogen source.
4. The method according to any one of claims 1 to 3, wherein: In step (1), the nitrogen source is at least one of acrylamide, urea, melamine, pyrrole, and ammonium chloride; Preferably, the mass percentage of the nitrogen source is 10-30%, based on the sum of the masses of the condensed aromatic hydrocarbon solid, the active component and the nitrogen source.
5. The method according to any one of claims 1 to 4, wherein: In step (1), calcination is carried out under normal pressure, with a heating rate of 1 to 10°C / min, a calcination temperature of 300 to 600°C, and a calcination time of 60 to 120 minutes.
6. The method according to any one of claims 1 to 5, wherein: In step (1), the oxidation is carried out under normal pressure, the oxidant is a peracid, the oxidation temperature is room temperature, and the oxidation time is 5 to 10 hours.
7. The method according to any one of claims 1 to 6, wherein: In step (1), the dialysis is performed at room temperature and pressure using a 1000 Dalton dialysis bag for 24 to 48 hours.
8. The method according to any one of claims 1 to 7, wherein: In the step (2), the activated carbon is at least one of coal-based activated carbon, fruit shell activated carbon, and coconut shell activated carbon; The soaking is carried out at normal temperature and pressure, the soaking temperature is 30 to 80° C., and the soaking time is 24 to 48 hours.
9. The method according to any one of claims 1 to 8, wherein: In step (3), the heating and drying temperature is 100 to 120° C.; In step (4), the high temperature calcination temperature is 400-800° C., the heating rate is 1-10° C. / min, and the calcination time is 5-12 hours.
10. Use of the catalyst obtained by the method according to any one of claims 1 to 9 in catalytic cracking of 1,2-dichloroethane to produce vinyl chloride.
Citation Information
Patent Citations
Supported nickel catalyst, preparation method and application of supported nickel catalyst in hydrogenation reaction of 1, 4-butynediol
CN113262794A
Monatomic catalyst for preparing vinyl chloride from 1, 2-dichloroethane as well as synthesis and application of monatomic catalyst
CN116251610A
Porous asphalt material as well as preparation method and application thereof
CN104874376A
Catalyst used in low-temperature removal of hydrogen chloride from dichloroethane for preparation of vinyl chloride, and preparation method and application thereof
CN105983428A
Coal asphalt porous polymer prepared through heteropolyacid catalysis as well as preparation method and application thereof
CN108517051A
Cited By
Dehydrochlorination catalyst as well as preparation method and application thereof
CN121927632A